Synthesis and crystal structure characterization of silicate apatite Sr2Y8(SiO4)6O2 - Shen, Yiqiang (2013)
Pure Sr2Y8(SiO4)6O2 powders were obtained after a solid-state reaction at 1400 °C for 6 h using the nanosized Y2O3, commercial SrCO3, and silica gel. The nanosized Y2O3 powder was synthesized by a precipitation method using Y(NO3)3 and NH4HCO3, followed by a heat treatment. The crystal structure of Sr2Y8(SiO4)6O2 was characterized by powder X-ray diffraction, Rietveld refinement, and high-resolution transmission electron microscopy. Results show that Sr2Y8(SiO4)6O2 has a typical apatite-type structure AI4AII6(BO4)6X2 in the P63/m space group. The lattice parameters are a=9.3884(6) Å and c=6.8657(4) Å. There are two special sites, AI (4f) and AII (6h), in the apatite structure. The AII sites are fully occupied by Y, while the AI sites are randomly filled by Y and Sr atoms. The crystallographic data obtained from Sr2Y8(SiO4)6O2 and other silicate oxyapatites are compared and summarized.